2014
DOI: 10.1016/j.jped.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low consumption of fruits and vegetables by preschoolers of low socio-economic level

Abstract: This study demonstrated a high prevalence of children who consumed less than one daily serving of fruit and vegetables; early feeding practices, parental education, and family income were associated with this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 23 publications
2
20
0
2
Order By: Relevance
“…A positive association between SSB consumption and overweight/obesity among preschoolers in the United States has also been noted (Welsh, 2005), whereas another U.S. study found an association between SSB consumption and growth faltering among preschoolers (Dennison, Rockwell, & Baker, 1997 (Denney et al, 2017;Rodríguez-Ramírez et al, 2016). Three of the remaining studies assessed nonrandom samples, including convenience samples of stunted children and mothers attending health services (Anderson et al, 2008;Roche et al, 2011;Valmórbida & Vitolo, 2014), limiting conclusions from these papers to wider populations. The four studies testing associations with nutritional outcomes also did not utilize representative samples-three studies systematically sampled mothers attending health centres for child health/vaccination services (Budree et al, 2017;Jimenez-Cruz et al, 2010;Vakili et al, 2015), and one included all children within catchment areas of selected health facilities (Faber, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive association between SSB consumption and overweight/obesity among preschoolers in the United States has also been noted (Welsh, 2005), whereas another U.S. study found an association between SSB consumption and growth faltering among preschoolers (Dennison, Rockwell, & Baker, 1997 (Denney et al, 2017;Rodríguez-Ramírez et al, 2016). Three of the remaining studies assessed nonrandom samples, including convenience samples of stunted children and mothers attending health services (Anderson et al, 2008;Roche et al, 2011;Valmórbida & Vitolo, 2014), limiting conclusions from these papers to wider populations. The four studies testing associations with nutritional outcomes also did not utilize representative samples-three studies systematically sampled mothers attending health centres for child health/vaccination services (Budree et al, 2017;Jimenez-Cruz et al, 2010;Vakili et al, 2015), and one included all children within catchment areas of selected health facilities (Faber, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although this review indicates that snack foods/SSB are potentially providing a substantial proportion of dietary energy among young children in LMIC, the low number of studies and their limited (Anderson et al, 2008;Karnopp et al, 2017;Lander et al, 2010;Valmórbida & Vitolo, 2014), and one was conducted in a conflict area (Jeharsae et al, 2011). Two studies used national datasets (Denney et al, 2017;Rodríguez-Ramírez et al, 2016); however, neither disaggregated data among 0-to 23-month-olds by rural/urban area of residence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was a methodological choice, as the dietary characteristics of Brazilian children in this age group have already been frequently analyzed (Carvalho et al, 2015;Valmórbida & Vitolo, 2014), as opposed to maternal perceptions about the subject which, as the present study shows, should be considered by professionals who provide health care to children and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Although only 0.2% of the children had diets considered good, 78% of the mothers reported believing that their children's diets were adequate (Kourlaba, Kondaki, Grammatikaki, RomaGiannikou, & Manios, 2009). Although the present study did not assess the food actually consumed by the children (since it focused on mothers' perceptions), national review studies (Carvalho, Fonsêca, Priore, Franceschini, & Novaes, 2015) using similar samples (Sparrenberger, Friedrich, Schiffner, Schuch, & Wagner, 2015), and other studies that considered data from the sample's main project from which the present study is derived (Valmórbida & Vitolo, 2014), indicate that children's diets fall well short of recommendations and do so at increasingly younger ages. Thus, it is noted that mothers' perceptions of the healthy feeding of their children may not be consistent with the food their children actually receive, as is indicated in the literature (Kourlaba et al, 2009).…”
Section: Maternal Perceptions Of Their Child's Dietsmentioning
confidence: 91%